Cell Therapy cGMP Facilities and Manufacturing - Gee, Adrian; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2009)
Cell Therapy: cGMP Facilities and Manufacturing is the source for a complete discussion of facility design and operation with practical approaches to a variety of day-to-day activities, such as staff training and competency, cleaning procedures, and environmental monitoring. This in-depth book also includes detailed reviews of quality, the framework of regulations, and professional standards. It meets a previously unmet need for a thorough facility-focused resource, Cell Therapy: cGMP Facilities and Manufacturing will be an important addition to the cell therapy professional's library. Additional topics in Cell Therapy: cGMP Facilities and Manufacturing... Standard operating procedures Supply management Facility equipment Product manufacturing, review, release and administration Facility master file This volume contains a collection of chapters authored by individuals who are active in the field of cell therapy product manufacturing. The collection and editing of these chapters was supported in part by the National Institutes of Health (National Heart, Lung and Blood Institute) program Production Assistance for Cellular Therapies (PACT).
I. Regulatory -- Regulation of Cell Product Manufacturing and Delivery: A United States Perspective -- The Regulatory Situation for Academic Cell Therapy Facilities in Europe -- A Regulatory System for Cell and Tissue Therapies: Proposed Approach in Australia -- II. GMP Facility Design -- University of Minnesota - Molecular and Cellular Therapeutics (MCT) -- University of Pittsburgh Cancer Institute - Hematopoietic Stem Cell Laboratory (HSC Lab)/Immunological Monitoring and Cellular Products Laboratory (IMCPL) -- Baylor College of Medicine - Center for Cell and Gene Therapy (CAGT) -- Design of a New GMP Facility - Lessons Learned -- III. Professional Cell Therapy Standards -- AABB Cell Therapy Standards -- Professional Standards for Cellular Therapies: Foundation for the Accreditation of Cellular Therapy (FACT) -- IV. Facility Operations -- Standard Operating Procedures -- Staffing, Training, and Competency -- Cleaning Procedures -- Environmental Monitoring -- Supply Management -- Facility Equipment -- Quality -- Product Manufacturing -- Product Review, Release, and Administration -- Use of a Facility Master File to Facilitate Regulatory Submissions for Cell Therapy Products.
Keywords: Cell biology; Cell Biology